A study to determine to what extent companies in South Africa are prepared to use corporate social responsibility as a developmental tool to alleviate poverty - Scholtz, Louise (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (School of Public Management and Planning))--University of Stellenbosch, 2009.